The Influence of Current Density on Transport of Vanadium Acetylacetonate through a Cation-Exchange Membrane. Issue 3 (1st March 2022) - Darling, Robert M.; Saraidaridis, James D.; Shovlin, Christopher; Fortin, Michael
Abstract : Fluxes of negatively charged, neutral, and positively charged vanadium acetylacetonates through the cation-exchange membrane Nafion® 211 were measured as functions of current density. Fluxes increase in order V(C5 H7 O2 )3 − < V(C5 H7 O2 )3 0 < V(C5 H7 O2 )3 + as expected for a membrane with fixed negative charges. Furthermore, the dependence of these fluxes on current density is quantitatively consistent with predictions made using independently measured conductivities in Nernst-Planck-Einstein transport equations. However, differences between the three fluxes are smaller than predicted by Donnan equilibrium calculations for Nafion 211 immersed in V(C5 H7 O2 )3 solutions. Specific interactions between sorbed species appear to be responsible for the relatively rapid transport of V(C5 H7 O2 )3 − compared to V(C5 H7 O2 )3 + .